Early Changes and Indicators Characterizing Lung Aging in Neonatal Chronic Lung Disease - Sucre, Jennifer; Haist, Lena; Bolton, Charlotte E.; Hilgendorff, Anne (Frontiers in Medicine, 2021)
Infants suffering from neonatal chronic lung disease, i.e. bronchopulmonary dysplasia, are facing long-term consequences determined by individual genetic background, presence of infections and postnatal treatment strategies such as mechanical ventilation and oxygen toxicity. The adverse effects provoked by these measures include inflammatory processes, oxidative stress, altered growth factor signaling and remodeling of the extracellular matrix. Both, acute and long-term consequences are determined by the capacity of the immature lung to respond to the challenges outlined above. The subsequent impairment of lung growth translates into an altered trajectory of lung function later in life. Here, knowledge about second and third hit events provoked through environmental insults are of specific importance when advocating lifestyle recommendations to this patient population. A profound exchange between the different health care professionals involved is urgently needed and needs to consider disease origin while future monitoring and treatment strategies are developed.